Peningkatan Hasil Belajar melalui Bahan Ajar Flipbook Siswa Sekolah Dasar - Rizki Sofyan Rizal (Arus Jurnal Pendidikan, 2022)
Education is a means to lead to the growth and development of the nation. Education can develop humans so that they are able to deal with any changes that occur due to advances in science and technology. Information and Communication Technology (ICT) is developing very rapidly along with the demands of various human needs. One of the important things that is directly related is the provision of innovative and creative learning resources in learning activities. To make it happen by developing electronic teaching materials such as flip books. The advantages of flip book teaching materials are that they are not monotonous and do not have to incur a lot of costs because they are in the form of soft files and make it easier for students to access learning anywhere and anytime according to the needs and opportunities of students, this is in accordance with learning tools in the 4.0 era. The use of teaching materials based on the flip book application makes students feel easy to understand the material because it is supported by illustrated pictures and videos both material and practice questions and is able to improve student learning outcomes. Keywords: Learning Outcomes, Flipbook Teaching Materials